THE EFFECT OF WAGES RATE, CAPITAL, AND NON-WAGE EXPENDITURE ON EMPLOYMENT OF SMALL MEDIUM ENTERPRISES (CASE STUDY OF CERAMICS INDUSTRY IN DINOYO, MALANG) - Putripuri, Anindi Galuh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Small and Medium Enterprises play an important role in Indonesia economy, in case SMEs mostly utilized local resources. SMEs have enough contribution to the Gross Domestic Product in Indonesia. However, the existence of SMEs still cannot reduce the higher number of unemployment in the country. In Malang City, there are a large number of SMEs that have potential to increase the number of employment, one of them is ceramics industry. This research has purpose to understand about the effect of wages rate, capital and non-wage expenditure to the employment in the ceramics industry in Dinoyo, Malang. The data used in this research is primary data, which gained from respondents through questionnaire and interview. Total sample collected was 30 units ceramics industry. The data processed with Eviews 7.0 with multiple regression analysis. The result of this study indicates that capital and non-wage expenditure have positive and significant effect on employment, while wages rate have negative and there is no significant effect to the employment in the Dinoyo’s ceramics industry.Keywords: SMEs, Wages Rate, Capital, Non-wage Expenditure, Employment.